THREE-DIMENSIONAL RESISTIVITY MODELING OF THE HYDROTHERMAL FLOW SYSTEM IN TANJUNG SAKTI PUMI REGION, INDONESIA - Marven Saputra; Suhendra Suhendra; Refrizon Refrizon; Florenzy Ernica Putra (Universitas Mataram, 2026)
Tanjung Sakti Pumi Subdistrict, Lahat Regency, South Sumatra Province, is characterized by surface geothermal manifestations, particularly hot springs associated with a hydrothermal system. This study aims to evaluate hydrothermal potential and subsurface fluid-flow patterns by analyzing resistivity variations using the Schlumberger Vertical Electrical Sounding (VES) method. An integrated interpretation combining one-dimensional (1D), two-dimensional (2D), and three-dimensional (3D) resistivity modeling was applied to improve subsurface characterization. The results reveal low-resistivity zones (< 6 Ωm), interpreted as clay-rich hydrothermal alteration layers (clay cap), while deeper, moderate-to-high-resistivity zones are associated with potential geothermal reservoirs. This multi-dimensional approach enhances the delineation of lateral and vertical continuity of conductive zones, providing a more comprehensive understanding of structurally controlled hydrothermal systems in the study area. The findings demonstrate the effectiveness of integrated resistivity modeling for preliminary geothermal exploration and offer important insights into subsurface geothermal structures in Tanjung Sakti Pumi.